2016
DOI: 10.1037/abn0000212
|View full text |Cite
|
Sign up to set email alerts
|

An Internet study of men sexually attracted to children: Sexual attraction patterns.

Abstract: To our knowledge, this is the first large study of the attractions of child-attracted men recruited in any manner other than their being charged with legal offenses. We recruited 1,189 men from websites for adults attracted to children. Men in our sample were highly attracted to children, and they were much less attracted to adults, especially to adult men. However, men varied with respect to which combination of gender and age they found most attractive. Men in our sample were especially attracted to pubescen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
47
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(54 citation statements)
references
References 24 publications
7
47
0
Order By: Relevance
“…By this, results of the current study confirm previous results 11, 33. Some researchers assume that the AOO implies information about the stability or persistence of sexual interest in children (eg, Grundmann et al 33 and Bailey et al 12 ). Comparable with the study by Tozdan and Briken, 11 the self-perceived flexibility of sexual interest in children also demonstrated variety (mean = 8.9, SD = 3.7).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…By this, results of the current study confirm previous results 11, 33. Some researchers assume that the AOO implies information about the stability or persistence of sexual interest in children (eg, Grundmann et al 33 and Bailey et al 12 ). Comparable with the study by Tozdan and Briken, 11 the self-perceived flexibility of sexual interest in children also demonstrated variety (mean = 8.9, SD = 3.7).…”
Section: Discussionsupporting
confidence: 89%
“…Among 75 men with self-identified sexual interest in children, our earlier study 11 found that self-perceived AOO ranged from 6 to 44 years with a mean value of 17 years. Bailey et al 12 recently published a study with a large sample of 1,189 men having sexual interest in prepubescent and/or pubescent children. The authors reported that “on average, participants recalled that they first realized their attraction to children ages 14 and younger at age 14.24 years (SD = 5.36).…”
Section: Introductionmentioning
confidence: 99%
“…Pedohebephilic men are sexually attracted to children of different genders and ages (Bailey, Hsu, & Bernhard, 2016;Blanchard et al, 2012;Blanchard et al, 2009). To facilitate a broad assessment of participants' overall degree of pedohebephilia and autopedophilia, we constructed general variables for sexual attraction to children and sexual arousal by the idea of being a child that were not specific to any gender-age category.…”
Section: Resultsmentioning
confidence: 99%
“…Due to the anonymous nature of the forum researchers were unable to mediate the impact of this by excluding those who have offended. The potential inclusion of offending MAPs may have impacted the themes identified as emerging research identifies disparities between these populations (Bailey et al, 2016). For example, offending MAPs report stronger attraction to children, possibly implicating differences in self-control between the populations (Cohen et al, 2018).…”
Section: Discussionmentioning
confidence: 99%